1986
DOI: 10.1073/pnas.83.24.9779
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor immunoreactivity in monoaminergic neurons of rat brain.

Abstract: A monoclonal antibody against the rat liver glucocorticoid receptor was used in combination with rabbit antibodies against tyrosine hydroxylase, phenylethanolamine N-methyltransferase, and 5-hydroxytryptamine to demonstrate strong glucocorticoid receptor immunoreactivity in large numbers of central monoaminergic nerve cell bodies of the male rat. The receptor immunoreactivity was predominantly located in the nucleus, whereas the tyrosine hydroxylase, phenylethanolamine N-methyltransferase, and 5-hydroxytryptam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
178
1
4

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(194 citation statements)
references
References 23 publications
11
178
1
4
Order By: Relevance
“…Here again, we have not detected a significant effect of dexamethasone on the stressinduced c-Fos expression on the lateral septum that has a high density of type II receptors (Magariños et al, 1989). On the other hand, we observed an effect of dexamethasone on the LC that has high reactivity to glucocorticoid receptors (Härfstrand et al, 1986).…”
Section: Dexamethasonecontrasting
confidence: 54%
“…Here again, we have not detected a significant effect of dexamethasone on the stressinduced c-Fos expression on the lateral septum that has a high density of type II receptors (Magariños et al, 1989). On the other hand, we observed an effect of dexamethasone on the LC that has high reactivity to glucocorticoid receptors (Härfstrand et al, 1986).…”
Section: Dexamethasonecontrasting
confidence: 54%
“…Glucocorticoid receptors are localized in brain monoaminergic neurons, particularly in the ventral tegmental (Härfstrand et al 1986), and these receptors have pivotal regulatory roles in many regions of the brain (De Kloet 1991; Joels and de Kloet 1992, 1994). Direct cellular interactions between stress hormones and dopamine neurons have been difficult to document; however, glucocorticoids can interact with dopamine reward circuitry in the basal forebrain that may be independent of direct glucocorticoid/dopamine interactions.…”
Section: Individual Differences and Rewardmentioning
confidence: 99%
“…Such stress hormones, via alterations of neuronal activity, consequently can induce neurobehavioral pathology. As noted above, dopaminergic neurons have receptors for glucocorticoids (Härfstrand et al 1986), and increases in the circulating levels of the hormones induce an increase of dopamine utilization in mesocorticolimbic neurons, an effect that is state-dependent (i.e., higher during the dark phase, or during food intake) (Piazza and Le Moal 1997). Thus, increases in corticosteroids renders animals more vulnerable to the acute reinforcing effects of drugs of abuse (Piazza and Le Moal 1997).…”
mentioning
confidence: 99%
“…Corticosterone administration has been shown to increase basal release of dopamine (DA) in the nucleus accumbens (Piazza et al, 1996b), whereas adrenalectomy reduces basal extracellular DA levels and blunts COC-induced DA increase in the same brain structure (Barrot et al, 2000). Evidence of a direct interaction between mesolimbic DAergic system and the HPA axis is further emphasized by the fact that glucocorticoid receptors (GRs) are expressed by DAergic neurons (Harfstrand et al, 1986) and that a glucocorticoid-responsive element (GRE) is found in the promoter region of the mouse tyrosine hydroxylase gene (Hagerty et al, 2001a, b).…”
mentioning
confidence: 99%